Diversity and conservation of mammals from Arequipa, Perú. - Zeballos Patrón, Horacio (2001)
This paper presents an updated list of terrestrial and marine mammal species that inhabit the Arequipa Department in Peru, based on revision of museum collections, field notes, and relevant literature. The mammal fauna is made up of 72 wild species in 54 genera, 20 families and six orders. Twenty three species are reported in the Department of Arequipa for the first time. In addition, 12 introduced species are listed. Finally, the conservation status of most of the species is discussed.